2005
DOI: 10.1213/01.ane.0000146521.68059.a1
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin System Inhibitors in a General Surgical Population

Abstract: We studied the relationship between the timing of discontinuing chronic angiotensin-converting enzyme inhibitors (ACEI) and angiotensin II receptor subtype 1 antagonists (ARA) and hypotension after the induction of general anesthesia in a general surgical population. We retrospectively studied 267 hypertensive patients receiving chronic ACEI/ARA therapy undergoing elective noncardiac surgery under general anesthesia. During preoperative visits, patients were asked to either take their last ACEI/ARA therapy on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
121
0
16

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(143 citation statements)
references
References 29 publications
6
121
0
16
Order By: Relevance
“…Comfere et al studied the relationship between the time of discontinuation of ACEI/ARA and hypotension immediately post induction (\ 30 min or less). 7 They found that patients who took these antihypertensives \ 10 hr before anesthesia had a significantly greater risk of moderate hypotension within 30 min of anesthesia induction. In contrast, we did not find more episodes of intraoperative hypotension in patients in the beach chair position who took ACEI/ARAs \ 10 hr before surgery; however, we analyzed the entire intraoperative period, not just the first 30 min (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comfere et al studied the relationship between the time of discontinuation of ACEI/ARA and hypotension immediately post induction (\ 30 min or less). 7 They found that patients who took these antihypertensives \ 10 hr before anesthesia had a significantly greater risk of moderate hypotension within 30 min of anesthesia induction. In contrast, we did not find more episodes of intraoperative hypotension in patients in the beach chair position who took ACEI/ARAs \ 10 hr before surgery; however, we analyzed the entire intraoperative period, not just the first 30 min (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension was defined as a single systolic blood pressure reading B 85 mmHg, according to the definition of Comfere et al 7 Blood pressure was measured with an oscillometric device or an arterial catheter and was recorded manually at least every five minutes. Arterial catheter transducers were placed at the level of the patient's heart.…”
Section: Methodsmentioning
confidence: 99%
“…These techniques include co‐induction, invasive arterial monitoring with titrated or prophylactic vasopressor therapy, depth‐of‐anaesthesia monitoring, beta‐blockers and the optimisation of stroke volume with intravascular fluid therapy. The omission of antihypertensive drugs, such as angiotensin‐converting enzyme inhibitors and receptor blockers, combined with the careful re‐introduction of these drugs after surgery, is common‐place and appears to be associated with fewer significant peri‐operative haemodynamic fluctuations 17. The introduction of peri‐operative beta‐blockade for high cardiac‐risk patients increases postoperative mortality, secondary to hypotension and stroke, albeit with less cardiac injury, as demonstrated in the POISE‐1 study 18.…”
Section: Blood Pressure Hypertension and Anaesthesiamentioning
confidence: 99%
“…23 Despite controversy regarding continuation of angiotensin converting enzyme inhibitors, this topic receives little consideration despite the high prevalence of concurrent chronic use of these medications. 24,25 The most controversial clinical issue in this arena is clearly the new institution of beta blockade for prophylactic purposes in previously naïve patients, which remains in the Class II category (either a or b). There is well publicized criticism of the ACCF/AHA Guidelines process that details an excessive reliance on Class II recommendations due to a lack of high quality available evidence and supports the clinical observation that Class II recommendations are quite weak (despite grouping into the IIa or IIb subcategories or the more cryptic estimates of certainty of treatment effect levels A, B, or C that are also applied).…”
mentioning
confidence: 99%
“…23 Malgré la controverse qui entoure le maintien des inhibiteurs de l'enzyme de conversion de l'angiotensine, ce sujet n'est que peu traité en dépit de la prévalence importante d'utilisation simultanée de ces médicaments sur une base chronique. 24,25 La question clinique la plus controversée dans ce domaine est clairement l'introduction du bêta-blocage à des fins prophylactiques chez des patients jusqu'alors naïfs, une indication qui demeure dans la catégorie de classe II (a ou b). Des critiques bien connues du processus d'élaboration des Directives de l'ACCF/AHA détaillent la confiance excessive accordée aux recommandations de classe I en raison de l'absence de données probantes de qualité.…”
unclassified